Geração de indicadores de produção e citação científica em revistas de Ciência da Informação: estudo aplicado à base de dados BRAPCI - Gabriel Junior, Rene Faustino [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The problem that arises in this research stems from the lack of research indicators based on national production to represent the current model of science in the field of information science produced in Brazil and represented in journals. The objective is to generate indicators of scientific output and citation from journals published in Brazil in the area of information science, using as source the Database of Scientific Journals in Information Science (Brapci). More specifically: to generate indicators of writers, topics and journals, and indicators of citations received, granted and self-citation; indices derived from citation, such as the impact factor, immediate impact, index h, half-life and obsolescence of literature; and compare indicators produced on bases of national and international data. It is a descriptive and methodological study that uses 1053 articles as corpus analysis published, ranging between 2012 and 2013. The collection of articles references consolidated a database of citations with approximately 27,000 references, of which 30% are from. The results of processed data were clustered to create the production's indicators and citation's indicators. The results highlight the growth of the area of Information Science, with a rate of 14.6% per year on average, which makes the production of articles to double every five years. The most productive authors and indicators of scientific collaboration were identified. Based on citations Impact Factors and h-index of periodicals were calculated. The values were compared with databases in order to try to describe the differences and accidents. It was not identified a direct relationship between the most productive and most cited authors, it was observed that a large number of authors, publishing a single article. Of citation indicators generated, demonstrated in compatibility with the bases, but there was no equality in the position of the most cited, concluding that depend...

O problema que se coloca nesta pesquisa deriva da inexistência de indicadores de pesquisa com base na produção nacional de forma a representar o modelo atual de ciência na área de Ciência da Informação produzida no Brasil e representada nos periódicos. O objetivo do estudo é gerar indicadores de produção e citação científica de periódicos publicados no Brasil, na área de Ciência da Informação, utilizando-se como fonte a Base de Dados de Periódicos Científicos em Ciência da Informação (Brapci). Mais especificamente: gerar indicadores da produção dos autores, temas e dos periódicos, e os índices de citações recebidas, concedidas e autocitação; os índices derivados de citação, tais como fator de impacto, impacto imediato, índice h, meia vida e obsolescência da literatura; e comparar indicadores produzidos em bases de dados nacionais e internacionais. Trata-se de um estudo descritivo e metodológico, que utiliza como corpus de análise 1.053 artigos publicados nos periódicos da área, compreendidos entre 2012 e 2013. A coleta das referências consolidou um banco de citações com, aproximadamente, 27.000 referências, das quais 30% utilizam o periódico como fonte. Os dados para produção dos indicadores foram concentrados o que possibilitou a geração dos indicadores de produção e citação. Dos resultados destaca-se o crescimento da área de Ciência da Informação, com um índice de 14,6% ao ano em média, o que faz a produção de artigos acumulados dobrarem a cada cinco anos. Identificaram-se os autores mais produtivos, e os indicadores de colaboração científica. Com base nas citações foram calculados os Fatores de Impacto e índice h dos periódicos. Os valores foram comparados com as bases de dados, de forma a tentar descrever as diferenças e acasos. Não se identificou relação direta entre os autores mais produtivos e os mais citados, observou-se que existe um grande número de autores que...
Keywords: Bibliometria; Pesquisa - Indicadores; Citações - Indicadores; Ciencia - Indicadores; Ciência da informação; Information science